2000
DOI: 10.1107/s0108768199014500
|View full text |Cite
|
Sign up to set email alerts
|

Packing effects on the geometry of neutral platinum(II) complexes due to solvate molecules: the structure of trans-dichlorobis(triphenylarsine)platinum(II)

Abstract: A series of structures of trans-dichlorobis(triphenylarsine)platinum(II), recrystallized from four different solvents, have been characterized by X-ray crystallography and were shown to crystallize as different solvates (same metal complex, different crystallization solvents). Their geometric differences induced by packing and solvent molecules were analysed with half-normal probability plots and root-mean-square deviations. The recrystallization solvents used in the investigation were 1,1,1-trichloroethane, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The methods used are based on those we and others have used previously. 2,13, 15 The total variance, σ, of a particular geometric parameter in a given ion is composed of two terms as in eqn. (1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods used are based on those we and others have used previously. 2,13, 15 The total variance, σ, of a particular geometric parameter in a given ion is composed of two terms as in eqn. (1).…”
Section: Methodsmentioning
confidence: 99%
“…In related work Englert and colleagues carried out a series of studies on tungsten, indium and cobalt complexes which show considerable variation in structure as a function of solvation and other aspects of the crystal environment. 14 Careful study of several solvates of a platinum() complex 15 and a series of studies using crystallographic and theoretical approaches in tin chemistry 16 have highlighted the effects of crystal packing on molecular geometry in specific systems.…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved in a number of ways, i.e. the study of crystal structures with more than one metal complex in the asymmetric unit (Lö vqvist, 1996), charged metal complexes with different counterions (Ericson et al, 1992), different crystalline solvates (Johansson et al, 2000) or different polymorphs (Kapoor et al, 1996). The structure of a toluene solvate of the title compound cis-PtCl 2 (Bz 2 S) 2 , where Bz 2 S is dibenzyl sulfide, is known (Braunmü hl et al, 1998) and here we report the structure of two polymorphs crystallizing in P " 1 1 and C2/c, respectively, with no solvate molecules.…”
Section: Introductionmentioning
confidence: 99%
“…These complexes form part of a class of symmetrical square-planar complexes that usually crystallize with the metal atom on a crystallographic inversion center, thus imposing a disordered packing arrangement (see Otto, 2001;Otto et al, 2000;Chen et al,1991, Kuwabara & Bau, 1994 for examples on Rh, Ir, Pd and Pt, respectively). Very often the Pt complexes display a trans geometry (Otto & Roodt, 1997;Johansson et al, 2000), but some number with a cis geometry have also been reported (Otto & Muller, 2001; Otto & Johansson, 2001). Pt(II) complexes, along with the Vaska-type complexes, are useful model complexes and provide several probing methods, e.g.…”
mentioning
confidence: 99%